Ibiza (Balearen), Spanien: Zum antiken Bleiglanzabbau am Puig de s’Argentera - Hermanns, Marcus H. (e-Forschungsberichte des DAI, 2023)
During the field work in 2013 different mining findspots within the area around the hill named s‘Argentera were examined. These were detected and catalogued in the course of the previously conducted prospecting works. The aim of the last campaign was to define the conservation status and the relative chronology of mining traces based only on the recognizable characteristics on the surface. Particular attention was paid to the possible identification of ancient mining traces, as for example the several times in old mining reports mentioned “roman works” (cf. Jorda et al., 2012).